Exploring entrepreneurial intentions in Latin American university students - Contreras Torres, Francoise; Espinosa Mendez, Juan Carlos; Soria Barreto, Karla; Portalanza Chavarría, Alexandra; Jáuregui Machuca, Kety; Omana Guerrero, Jesús Alfonso (Universidad de San Buenaventura, 2017)
The aim of this study was to determine if entrepreneurial intention, based on Ajzen’s model of planned behavior (1991), can be predicted by risk propensity, internal locus of control and leadership skills. Six standardized and reliable instruments were applied to 1493 undergraduate university business students in Latin American countries, selected through non-random quota sampling in accordance with their formation level in each of the five participating universities. Using structural equation techniques, the research model was validated and intention estimated and analyzed in relation to a set of socio-demographic variables. According to the results, entrepreneurial intention can be significantly predicted by the psychological variables under consideration and, contrary to what has been reported in other research, no gender differences were found in the intention of entrepreneurship. These findings are discussed.

El propósito de este estudio fue determinar si la intención de emprendimiento, con base en el modelo de comportamiento planeado de Ajzen (1991), puede predecirse con base en la propensión al riesgo, el locus de control interno y las habilidades de liderazgo. Asimismo, se identificaron variables sociodemográficas asociadas a tal intención. Se aplicó una batería de instrumentos estandarizados y confiables a 1493 estudiantes universitarios de áreas empresariales en cinco países latinoamericanos. De acuerdo con los resultados, la intención de emprendimiento puede predecirse significativamente con las variables estudiadas. De igual forma, se confirmó la incidencia de los antecedentes familiares en tal intención lo cual ha sido reportado en varios estudios. Contrario a lo hallado en otros estudios, no se encontraron diferencias por género en la intención de emprendimiento. Se discuten estos hallazgos.
Keywords: Entrepreneurial intention; Leadership skills; Intención de emprendimiento; Locus of control; Habilidades de liderazgo; Risk propensity; Locus de control; Propensión al riesgo; Latin American students; Estudiantes latinoamericanos; https://purl.org/pe-repo/ocde/ford#5.02.04